Factors Affecting Students' Self-Efficacy Beliefs in Moroccan Higher Education - Otmane Omari; Mohammed Moubtassime; Driss Ridouani (National Research University Higher School of Economics, 2020)
Self-efficacy, or confidence in one's ability to do a task, is a key element that affects students' motivation and performance. For that reason, the main purpose of this study was to collect specific information about students' self-efficacy and factors affecting it. This includes comparing the differences between three Moroccan universities representing public and private institutions in terms of students' self-efficacy. A sample of 365 undergraduate students responded to the questionnaire on self-efficacy for self-regulated learning on a 5-point Likert scale. The findings demonstrate that students' level of self-efficacy is moderate. With regard to the differences between the three universities, a slight difference was found in favor of the private one. Meanwhile, third-year students reported greater self-efficacy than first and second-year students. However, no statistically significant differences were found between male and female students. More importantly, the results reveal that students' living circumstances during the academic year and their initial motive behind enrolling in university affected their self-efficacy beliefs. Overall, this study provides teachers and practitioners with insights about self-efficacy that could be used to promote students' success in Moroccan universities.